2017
DOI: 10.3168/jds.2016-11197
|View full text |Cite
|
Sign up to set email alerts
|

Determination of energy and protein requirements for crossbred Holstein × Gyr preweaned dairy calves

Abstract: The objective was to quantify the energy and protein nutritional requirements of Holstein × Gyr crossbred preweaned dairy calves until 64 d of age. Thirty-nine Holstein × Gyr crossbred male calves with an average initial live weight (mean ± SEM; for all next values) of 36 ± 1.0 kg were used. Five calves were slaughtered at 4 d of life to estimate the animals' initial body composition (reference group). The remaining 34 calves were distributed in a completely randomized design in a 3 × 2 factorial arrangement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…Efficiency of use of metabolizable energy for pregnancy was estimated by the iterative method. The obtained value for k preg was 14.1 ± 0.41%, which is very close to values obtained by Ferrell et al [1], 14%; Lage [40], 12.5% and BR-CORTE [4], 12%. The NRC [6] uses k preg suggested by Ferrell et al [1].…”
Section: Plos Onesupporting
confidence: 88%
See 2 more Smart Citations
“…Efficiency of use of metabolizable energy for pregnancy was estimated by the iterative method. The obtained value for k preg was 14.1 ± 0.41%, which is very close to values obtained by Ferrell et al [1], 14%; Lage [40], 12.5% and BR-CORTE [4], 12%. The NRC [6] uses k preg suggested by Ferrell et al [1].…”
Section: Plos Onesupporting
confidence: 88%
“…Lage [ 40 ] found NE preg , represented by retained energy in gravid uterus and mammary gland for Holstein × Gyr cows of 2.70, 2.71, and 2.88 Mcal/day at 180, 210 and 240 days of pregnancy, respectively. Net energy requirements obtained by Lage [ 39 ] are closer to NRC [ 6 ] when compared to our values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The breed’s performance in Southeast Asian countries ranges from 1710 to 1978 kg of milk/lactation [ 36 , 54 ]. Another well-established breed is the Holstein × Gyr breed, where several requirement and feed efficiency studies have been conducted in recent years [ 55 , 56 , 57 ]. The breed was observed to produce an average milk yield of 5118 and 5211 kg/lactation of 1/2 and 7/8 Holstein composition, respectively [ 38 ].…”
Section: Temperate–tropical Crossbreeding Endeavors In Developing Countries In the Tropicsmentioning
confidence: 99%
“…Blome et al (2003) and Bartlett et al (2006) demonstrated that increasing dietary CP in milk replacer increased lean tissue gain and decreased fat content of empty body (EB) gain. However, few studies have determined changes of body composition and EB gain in calves fed both starter feed and milk or milk replacer (Meyer, 2005;Silva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%